The Application of KNN Algorithm in Optimizing Urban Land Use with an Emphasis on Earthquake Risk, Case study: Sanandaj City - Shahrivar rostaei; Rahim heydari chyaneh; ayoub zoghi (تحقیقات کاربردی علوم جغرافیایی)
The occurrence of earthquakes and the losses and damages caused by it have always imposed a serious threat to the city, residents and assets, so that it has made planners and city managers to provide logical and scientific solutions to make cities safer. Securing cities against earthquakes will not be achieved only by creating strong structures, and we must take steps to reduce urban vulnerability through optimizing urban land use. The purpose of this study is to determine the optimal urban areas for the development of the city with the aim of reducing the vulnerability of Sanandaj. For this purpose, KNN method has been used as a model with relatively high accuracy to evaluate the optimal land use of Sanandaj city with an emphasis on earthquake risk. The obtained model output shows that about 32% of the city area is in optimal condition and district 2 with 42.78% equivalent to 406 hectares and district 4 with 50.85% equivalent to 658 hectares provide an optimal condition for the development of the city, towards reducing urban vulnerability and increasing urban land use optimization. The general condition of the city is not suitable in terms of optimality and the neighborhoods located in districts 1 and 2 are in a very inappropriate condition due to high population and residential density, very poor permeability and low adaptation of land uses. In evaluating the model, the value of the area below the curve is 0.951, which indicates the desirable performance of the model in examining the subject.